Living with aids and psychological suffering - Maria Angélica Pagliarini Waidman; Jacqueline Botura Bessa; Fernanda Lorena Canton da Silva (Rev Rene)
This is a bibliographical study of qualitative nature and it aims to identify the presence of psychological suffering in the bearers of the Aids virus and to understand the process of nursing care to those people, in the existent national literature on AIDS/HIV. The selection of material was carried out in the LILACS, BDENF, SCIELO, BVS database whose works were published between 1980 and 2009. The analysis of the material provided a category named: “Being with Aids and not losing the reason... the feelings after the diagnosis and living with the disease” and four subcategories. We verified that living with the disease makes people hostage to multiple undesirable feelings which lead them to mental suffering. People who are infected with HIV have daily difficulties in all aspects of their lives. Therefore, qualified health professionals are required to provide them support by means of integral and individualized care.